Single-Stage Ear Reconstruction and Hearing Restoration Using Polyethylene Implant and Implantable Hearing Devices - Hempel, John Martin (Facial Plastic Surgery, 2015)
The use of porous polyethylene in reconstructive surgery of the auricle is becoming increasingly accepted. This is a single-stage procedure providing pleasing cosmetic rehabilitation. Further advantages are the possibility of early implantation and the lack of complications caused by harvesting costal cartilage. Additional hearing restoration using middle ear implants allows functional rehabilitation at an early stage.
Keywords: ear reconstruction; atresia; microtia; porous polyethylene; middle ear implants